Adding Depth to Our Understanding of Nitrogen Dynamics in Permafrost Soils. Issue 8 (22nd August 2018) - Salmon, Verity G.; Schädel, Christina; Bracho, Rosvel; Pegoraro, Elaine; Celis, Gerardo; Mauritz, Marguerite; Mack, Michelle C.; Schuur, Edward A. G.
Abstract: Losses of C from decomposing permafrost may be offset by increased productivity of tundra plants, but nitrogen availability partially limits plant growth in tundra ecosystems. In this soil incubation experiment carbon (C) and nitrogen (N) cycling dynamics were examined from the soil surface down through upper permafrost. We found that losses of CO2 were negatively correlated to net N mineralization because C‐rich surface soils mineralized little N, while deep soils had low rates of C respiration but high rates of net N mineralization. Permafrost soils released a large flush of inorganic N when initially thawed. Depth‐specific rates of N mineralization from the incubation were combined with thaw depths and soil temperatures from a nearby manipulative warming experiment to simulate the potential magnitude, timing, and depth of inorganic N release during the process of permafrost thaw. Our calculations show that inorganic N released from newly thawed permafrost may be similar in magnitude to the increase in N mineralized by warmed soils in the middle of the profile. The total release of inorganic N from the soil profile during the simulated thaw process was twice the size of the observed increase in the foliar N pool observed at the manipulative experiment. Our findings suggest that increases in N availability are likely to outpace the N demand of tundra plants during the first 5 years of permafrost thaw and may increase C losses from surface soils as well as induce denitrification and leaching of N from these ecosystems. Plain Language Summary: Arctic plants are rooted in an active layer of soil that thaws during the summer months and is often nutrient‐poor because of slow decomposition in these cold ecosystems. Beneath the active layer, there is a layer of soil that remains frozen year‐round (permafrost). In this experiment, we collected soil cores that spanned the entire active layer and upper permafrost and incubated these soils in the lab so we could monitor their decomposition. We focus on nitrogen cycling because this is a key nutrient for the growth of arctic plants and soil microbes. We found nitrogen availability was low in shallow surface soils but high deep in the active layer and permafrost. Our results show that arctic warming will impact nitrogen release from two locations in the soil profile: at the bottom of the soil profile when nitrogen‐rich permafrost soil thaws for the first time and with the active layer when decomposition is accelerated by warmer temperatures. Our calculations suggest that these two sources of nitrogen are similar in size during the first five years of permafrost thaw, exceed plant demand for nitrogen, and are likely to contribute to losses of nitrogen from warming arctic ecosystems. Key Points: Soil microbes are nitrogen (N) limited in surface soils, but deeper layers are N rich; permafrost thaw will alter this stratification Warming will release inorganic N (1) by thawing N‐rich permafrost and (2) by accelerating N mineralization within active layer soils These two sources of inorganic N are similar in magnitude during the first 5 years of thaw and together exceed plant N demand